Database of Nutrition Status, Production and Reproduction Performance, and Social Economy of a Farmer of a Beef Cattle Farm in Sumberpucung District, Malang Regency - Mashudi; Rizki Prafitri; Nanang Febrianto; Aulia Puspita Anugra Yekti; Asri Nurul Huda; Poespitasari Hazanah Ndaru; Trinil Susilowati (Faculty of Animal Science, Universitas Brawijaya, 2022)
Sumberpucung District, Malang Regency has the potential for developing beef cattle. This study aimed to analyze the nutrition status, production, and reproduction performance of beef cattle as well as examine the socio-economic of farmers. The research method is a survey to obtain a database about beef cattle kept by a farmer. This study involved 50 respondents spread over 4 villages, namely Senggreng, Jatiguwi, Trenyang, and Sambigede. The results of the research showed that the average age of farmers was only 14% who were under 40 years old. The number of cattle ownership was an average of 2-3 heads with the largest breed of cattle being Simmental crossbreeds. The system of breeding and rearing was wholly AI and in the cage. Feed that was usually given in general was rice straw followed by corn straw, sugarcane top, elephant grass, field grass, and rice bran. The average feed intake of rice straw, corn straw, and elephant grass were 17.865 – 22.9 kg/head/day, 10.23 – 20.5 kg/head/day, and 17-31.3 kg/head/day respectively. The chest girth of the male adult group had the highest value of 162.5 cm and the female adult group of 165.7 cm. The highest estimated live weights for male and female adults in Jatiguwi village were 340.40 kg and 352.31 kg respectively. The highest and the lowest average gestation length were 235 days and 224 days respectively. The highest and the lowest average of S/C were 5.5 times and once. The average calving interval of a cow in Senggreng, Trenyang, Sambigede, and Jatiguwi villages were 440 days, 399 days, 420 days, and 403 days respectively. The number of cattle that were pregnant in the first AI, second AI, and more than the second AI were 27 heads, 32 heads, and 24 heads. Based on the type of feed and its intake, it can be said that the nutrition status of beef cattle in Sumberpucung District is highly good. Effects of nutrition status can be seen from the performance of production and reproduction of cattle in terms of chest girth, live weight, and calving interval.